Proposed instructional materials in beginning reading in Pilipino for educable mentally retarded - Balbalec, Feleora G. (Quezon City College of Education, University of the Philippines Diliman, 1971)
The aim of the study is to present instructional materials in beginning reading in Pilipino for the educable mentally retarded using the synthetic approach. The primary method used to obtain data is library research. This is supplemented by the writer's personal observations and interviews. The activities found in the proposed materials are suggestive in nature and as long as the principle behind the synthetic method is retained, the teacher is free to create activities to suit the particular needs, limitations and interests of her pupils.
Thesis (Master of Arts in Teaching : Special Education-Mentally Retardation)--University of the Philippines, Diliman.
Keywords: Reading (Primary) -- Philippines; Filipino language -- Study and teaching (Primary); Children with mental disabilities -- Education (Primary) -- Philippines; Teaching -- Philippines -- Aids and devices